The Prohibition Of Interfaith Marriage In Fiqhiyah Rules: An Analysis Of The Constitutional Court Decision Number 212/Puu-XXIII/2025 - Aripin Marpaung; Fauzan Nazila; Maulidin; Wahyu Setiawan Rambe; Muhammad Hafizh Hariri Lubis; Muhammad Hafiz Nur Hasibuan; Maulana Kesuma (UNIVERSITAS PAKUAN, 2026)
The prohibition of interfaith marriage in Islamic jurisprudence (fiqh) is rooted in definitive Quranic texts and scholarly consensus (ijma'). However, in the Indonesian legal context, this issue is not only a matter of religious validity but also involves the administrative registration of marriage by the state. Constitutional Court Decision Number 212/PUU-XXIII/2025 emerged in response to a judicial review petition against Article 2(1) of Law Number 1 of 1974 on Marriage, filed by a Muslim civil servant who intended to marry a Christian woman. This research aims to examine fiqhiyah rules regarding the prohibition of interfaith marriage, analyze the Constitutional Court's legal considerations in Decision Number 212/PUU-XXIII/2025, and assess whether the decision is consistent with fiqhiyah rules. This research uses a normative juridical method with a statute approach, conceptual approach based on fiqhiyah rules and maqashid shariah, and a case approach. The results show that fiqhiyah rules explicitly prohibit interfaith marriage, particularly through the established fiqhiyah maxim لَا يَجُوزُ نِكَاحُ الْمُسْلِمَةِ مِنْ كَافِرٍ (it is not permissible for a Muslim woman to marry a non-Muslim man), supported by QS. Al-Baqarah: 221 and the ijma' of scholars from the four major madhabs. The Constitutional Court in its decision affirmed that the validity of marriage is the domain of religion, not the state, and rejected the petition entirely. There is normative consistency between the fiqhiyah prohibition and the Court's decision in terms of not legalizing interfaith marriage through religious law. However, a normative tension remains regarding the administrative recording of interfaith marriages that have been declared valid under their respective religious laws. The maqashid shariah approach particularly hifz al-din and hifz al-nasl supports the fiqhiyah prohibition while also demanding legal certainty for the civil rights of citizens.